Transport of hop aroma compounds across Caco-2-monolayers. - Heinlein, Anja; Metzger, Marco; Walles, Heike; Büttner, Andrea (Food and Function, 2014)
Although being reported and used as a sedative remedy for several years, the bioactive principle of hop preparations is still not decisively clarified. Understanding absorption and transformation processes of potential physiologically active constituents is essential to evaluate the likeliness of biological effects on humans. Therefore, single hop aroma compounds as well as digestive transformation products thereof have been investigated in view of their human intestinal absorption, applying Caco-2 transport experiments as well as investigations on potential biotransformation processes. Selective and sensitive identification and quantification were thereby achieved by application of two-dimensional high resolution gas chromatography-mass spectrometry in conjunction with stable isotope dilution analysis, leading to the determination of apparent permeability values by different mathematical approaches considering sink and non-sink conditions. Overall, calculated permeability values ranged from 2.6 × 10(-6) to 1.8 × 10(-4) cm s(-1) with all mathematical approaches, indicating high absorption potential and almost complete bioavailability for all tested compounds with hydroxyl-functionalities. Considering this high permeability together with the high lipophilicity of these substances, a passive transcellular uptake route can be speculated. Investigated sesquiterpenes and β-myrcene showed flat absorption profiles while the investigated esters showed decreasing profiles. In view of the lipophilic and volatile nature of the investigated substances, special attention was paid to recovery and mass balance determination. Furthermore, in the course of the transport experiments of 1-octen-3-ol and 3-methyl-2-buten-1-ol, additional biotransformation products were observed, namely 3-octanone and 3-methyl-2-butenal, respectively. The absence of these additional substances in control experiments strongly indicates an intestinal first-pass metabolism of the α,β-unsaturated alcohols 1-octen-3-ol and 3-methyl-2-buten-1-ol in Caco-2 cells.<br